Asia and Europe in the 21st century : new anxieties, new opportunities - Mishra, Rahul, Ph. D. (Abingdon, Oxon ; New York, NY : Routledge, 2021)
'How are the rising mutual concerns of Asian and European countries shaping their approaches to the international order? Contributors to this volume discuss emerging critical issues in International relations, including the Indo-Pacific constructs, China's Belt and Road Initiative (BRI), and the progress of established regional security mechanisms like the Shanghai Cooperation Organisation. They also compare western and non-western approaches to these issues, with a holistic perspective on the origins and evolutions of these approaches. Both the Indo-Pacific constructs and BRI present a remarkable set of opportunities for Europe as well as Asia. This book presents key implications of the changing politico-security dynamics in the two regions from the perspectives of both Asian and European scholars and theoretical traditions. This volume is a must-read for scholars of International Relations with a focus on relations between Asia and Europe'--
OCLC-licensed vendor bibliographic record.
Keywords: Security, International; Asia -- Foreign relations; Europe -- Foreign relations